Multivalent Nanosheet Antibody Mimics for Selective Microbial Recognition and Inactivation. Issue 22 (23rd April 2021) - Kang, Tae Woog; Hwang, In‐Jun; Lee, Sin; Jeon, Su‐Ji; Choi, Chanhee; Han, Juhee; So, Yoonhee; Son, Wooic; Kim, Hyunsung; Yang, Chul‐Su; Park, Jae‐Hyoung; Lee, Hwankyu; et al.
Abstract: Antibodies are widely used as recognition elements in sensing and therapy, but they suffer from poor stability, long discovery time, and high cost. Herein, a facile approach to create antibody mimics with flexible recognition phases and luminescent rigid scaffolds for the selective recognition, detection, and inactivation of pathogenic bacteria is reported. Tripeptides with a nitriloacetate‐Cu group are spontaneously assembled on transition metal dichalcogenide (TMD) nanosheets via coordination bonding, providing a diversity of TMD‐tripeptide assembly (TPA) antibody mimics. TMD‐TPA antibody mimics can selectively recognize various pathogenic bacteria with nanomolar affinities. The bacterial binding sites for TMD‐TPA are identified by experiments and molecular dynamics simulations, revealing that the dynamic and multivalent interactions of artificial antibodies play a crucial role for their recognition selectivity and affinity. The artificial antibodies allow the rapid and selective detection of pathogenic bacteria at single copy in human serum and urine, and their effective inactivation for therapy of infected mice. This work demonstrates the potential of TMD‐TPA antibody mimics as an alternative to natural antibodies for sensing and therapy. Abstract : Multivalent nanosheet artificial antibodies with high selectivity and strong binding affinity to pathogenic bacteria are created by spontaneous assembly of various tripeptide recognition phases on transition metal dichalcogenide nanosheets. The luminescent antibody mimics can detect pathogenic bacteria at a single‐cell level from human serum and urine and effectively inactivate them on wounds of infected mice for healing.